C-Reactive Protein and Ferritin Are Associated With Organ Dysfunction and Mortality in Hospitalized Children. (June 2019) - Horvat, Christopher M.; Bell, Jamie; Kantawala, Sajel; Au, Alicia K.; Clark, Robert S. B.; Carcillo, Joseph A.
Our objective was to determine if C-reactive protein (CRP) and ferritin values alone and in combination are associated with mortality among hospitalized children. All hospitalized patients at our institution with a CRP or ferritin assay in 2015 and 2016 were included. Area under the receiver operating curves (AUROC) were examined, optimal cut-points determined, and patients were stratified into low-, intermediate-, or high-risk groups based on elevation of zero, one, or both biomarkers. A total of 14 928 CRP and 653 ferritin values were obtained, with both obtained for 172 patients. AUROC for maximum CRP value was 0.76 (0.68-0.85) with a cut-point of 7.1 mg/dL for in-hospital mortality and 0.90 (0.83-0.98) for maximum ferritin with a cut-point of 373 ng/mL. Elevation of both ferritin and CRP was associated with the highest inpatient mortality (21.7%) and greatest organ dysfunction, followed by either biomarker alone. Additional prospective study of these biomarkers in combination is warranted.